Transient Analysis of Plasmonic Nanostructures using an MOT-PMCHWT Solver - Uysal, Ismail E.; Ulku, H. Arda; Bagci, Hakan (IEEE, 2015)
A marching on in time (MOT) scheme for solving the Poggio-Miller-Chan-Harrington-Wu-Tsai (PMCHWT) surface integral equation on plasmonic nanostructures is described. The proposed scheme calls for temporal convolutions of the permittivity and Green function of the plasmonic medium with the temporal basis function. Time domain samples of the permittivity and the Green function required by these convolutions are computed using a fast relaxed vector fitting (FRVF) algorithm. Numerical results demonstrate the accuracy and applicability of the proposed MOT-PMCHWT solver.
IEEE International Symposium on Antennas and Propagation / USNC/URSI National North American Radio Science Meeting -- JUL 19-24, 2015 -- Vancouver, CANADA